Assessment of reading in english as foreign language: investigating the defensibility of test items - Tumolo, Celso Henrique Soufen (2005)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.